MENGANGKAT POTENSI UBI MADU DENGAN STRATEGI PEMASARAN KREATIF: STUDI KASUS UBIQUE - Muhammad Rafly Raihan Dimyanto (Cahaya Ilmu Bangsa, 2025)
This study analyzes the marketing strategy of an innovative sweet potato-based product, Ubique (Ubi Crème Brûlée), with a 4P Marketing Mix approach (Product, Price, Place, Promotion). Ubique is a snack made from local honey sweet potatoes combined with international techniques in the style of crème brûlée. This study uses a qualitative approach with a case study method through interviews, observations, and product promotion analysis. The findings of the study show that the combination of product innovation that combines local ingredients with international flavors, competitive premium prices, digital and physical distribution strategies, and social media-based promotions are key factors for Ubique's success in the Surabaya market. This marketing strategy opens up opportunities for further development in expanding market reach and enhancing Ubique's competitiveness in the local ingredients-based healthy food industry